Neuroprotective Effects of Isosteviol Sodium in Murine Brain Capillary Cerebellar Endothelial Cells (cerebEND) After Hypoxia - Rösing, Nils; Salvador, Ellaine; Güntzel, Paul; Kempe, Christoph; Burek, Malgorzata; Holzgrabe, Ulrike; Soukhoroukov, Vladimir; Wunder, Christian; Förster, Carola (Frontiers in Cellular Neuroscience, 2020)
Ischemic stroke is one of the leading causes of death worldwide. It damages neurons and other supporting cellular elements in the brain. However, the impairment is not only confined to the region of assault but the surrounding area as well. In addition, it also brings about damage to the blood brain barrier (BBB) which in turn leads to microvascular failure and edema. Hence, this necessitates an on-going, continuous search for intervention strategies and effective treatment.Of late, the natural sweetener stevioside proved to exhibit neuroprotective effects and therapeutic benefits against cerebral-ischemia induced injury. Its injectable formulation, isosteviolsodium (STVNa) also demonstrated favorable results. Nonetheless, its effects on the BBB have not yet been investigated to date. As such, this present study was designed to assess the effects of STVNa in our in vitro stroke model of the BBB.The integrity and permeability of the BBB are governed and maintained by tight junction proteins (TJPs) such as claudin-5 and occludin. Our data show increased claudin-5 and occludin expression in oxygen and glucose (OGD)-deprived murine brain capillary cerebellar endothelial cells (cerebEND) after STVNa treatment. Likewise, upregulation of the transmembrane protein integrin-v was also observed. Finally, cell volume was reduced with simultaneous administration of STVNa and OGD in cerebEND cells.In neuropathologies such as stroke, the failure of cell volume control is a major feature leading to loss of cells in the penumbra as well as adverse outcomes. Our initial findings therefore point to the neuroprotective effects of STVNa at the BBB in vitro, which warrant further investigation for a possible future clinical intervention.